2015
DOI: 10.3746/jkfn.2015.44.12.1918
|View full text |Cite
|
Sign up to set email alerts
|

Quality Characteristics and Antioxidant Properties of Yanggaeng Supplemented with Hallabong Powder

Abstract: The feasibility of incorporating Hallabong powder (HP) as a value-added food ingredient into convenient food products was investigated using yanggaeng as a model system. HP was incorporated into yanggaeng at amounts of 0, 2, 4, 6, and 8% (w/w) based on total weight of cooked white beans and HP. pH level decreased while soluble solid content increased significantly with increasing levels of HP (P<0.05), whereas moisture content was not directly affected by level of HP incorporation. In terms of color, lightness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Therefore, research on Yanggaeng production, which includes various natural ingredients with physiological benefits, has become more active. For example, studies have reported adding ingredients such as barley sprouts [10], black ginger [11], finger root powder [12], tomatoes [3], mugwort powder [13], aronia juice [1], Enteromorpha prolifera [14], Hallabong orange [15], green tea powder [16], and paprika [17] to enhance the nutrition density and physiological properties of Yanggaeng.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, research on Yanggaeng production, which includes various natural ingredients with physiological benefits, has become more active. For example, studies have reported adding ingredients such as barley sprouts [10], black ginger [11], finger root powder [12], tomatoes [3], mugwort powder [13], aronia juice [1], Enteromorpha prolifera [14], Hallabong orange [15], green tea powder [16], and paprika [17] to enhance the nutrition density and physiological properties of Yanggaeng.…”
Section: Introductionmentioning
confidence: 99%